Glucose-fatty acid interaction in skeletal muscle and adipose tissue in insulin resistance - Cahová, M; Vavřínková, H; Kazdová, L (Physiological research, 2007)
Insulin resistance (IR) is the result of long-lasting positive energy balance and the imbalance between the uptake of energy rich substrates (glucose, lipids) and energy output. The defects in the metabolism of glucose in IR and type 2 diabetes are closely associated with the disturbances in the metabolism of lipids. In this review, we have summarized the evidence indicating that one of the important mechanisms underlying the development of IR is the impaired ability of skeletal muscle to oxidize fatty acids as a consequence of elevated glucose oxidation in the situation of hyperglycemia and hyperinsulinemia and the impaired ability to switch easily between glucose and fat oxidation in response to homeostatic signals. The decreased fat oxidation results into the accumulation of intermediates of fatty acid metabolism that are supposed to interfere with the insulin signaling cascade and in consequence negatively influence the glucose utilization. Pathologically elevated fatty acid concentration in serum is now accepted as an important risk factor leading to IR. Adipose tissue plays a crucial role in the regulation of fatty acid homeostasis. The adipose tissue may be the primary site where the early metabolic disturbances leading to the development of IR take place and the development of IR in other tissues follows. In this review we present recent evidence of mutual interaction between skeletal muscle and adipose tissue in the establishment of IR and type 2 diabetes.
Keywords: mastné kyseliny; tuková tkáň; Insulin Resistance; kosterní svaly; malonylkoenzym A; Glucose; Muscle, Skeletal; Animals; inzulinová rezistence; lidé; glukosa; Adipose Tissue; Fatty Acids; Humans; zvířata; Malonyl Coenzyme A